TRANSFORMATION CHARACTERISTICS OF UZBEK NATIONAL MARRIAGE CEREMONIES AND ITS SPIRITUAL IMAGE (Scientific journal of the Fergana State University, 2023)
In this article, it is emphasized that family and marriage have been considered a sacred Motherland in our country since ancient times. It is stated that the factors that make changes in Uzbek marriage ceremonies are the desire for a modern lifestyle and changes in society, in particular, the deepening of the market economy.